Sufism, mystics, and saints in modern Egypt - Hoffman, Valerie J. (Valerie Jon), 1954- (Studies in comparative religion (Columbia, S.C.), 1995)
For centuries Sufism - Islamic mysticism - held a major place in Islamic spirituality, intellectual life, and popular religion. While many twentieth-century observers have commented on Sufism's decline, and modernists and fundamentalists alike have criticized the movement, few scholars have analyzed present-day Egyptian Sufism as a system in its own right rather than as a degradation of the classical ideal. Drawing on detailed fieldwork and on textual analysis of a variety of little-known recent and medieval sources, Valerie J. Hoffman presents Sufism as it exists in Egypt today, in the vivid experiences of its adherents, from humble housewives to famous mystics and saints. With an array of conclusions that overturn widely held beliefs about modern Sufis, Hoffman argues that the apparent assimilation of Egyptian Sufism masks a thriving movement hidden from the Western world.